Understanding Information Technology and Accounting Has a Moderated Effect on Organizational Commitment - Zarkasi Zarkasi; Syamsu Rijal; Iswahyuningsih Iswahyuningsih; Dewi Ratih K (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of understanding information technology and accounting on organizational commitment with the quality of human resources as a moderating variable. The sample in this study amounted to 44 respondents. The analytical methods used in this study, namely data quality test, classical assumption test, multiple linear regression analysis test, partial test, simultaneous test, and moderated regression analysis with the help of SPSS version 23. The results of this study concluded that information technology partially influences positive effect on organizational commitment, while accounting understanding has a negative effect and does not succeed in giving a significant effect on organizational commitment. As well as the simultaneous test results of information technology and understanding of accounting together influence organizational commitment. Meanwhile, after being moderated by the quality of human resources, only information technology variables have a positive effect on organizational commitment. This is because the moderating variable contributes to supporting the understanding of information technology, the more qualified human resources an agency is, the more capable it is to understand technological developments that continue to evolve. Meanwhile, accounting understanding after being moderated by the quality of human resources, did not succeed in having a positive influence on organizational commitment. This is because the synthesis of human resource quality moderation is still not in accordance with the existing implementation in agencies.